Techno-economic and environmental assessment of bioethanol production from high starch and root yield Sri Kanji 1 cassava in Malaysia - Hanif M.; Mahlia T.M.I.; Aditiya H.B.; Chong W.T.; Nasruddin (Elsevier Ltd, 2023)
Alternative fuels; Carbon; Carbon dioxide; Cost benefit analysis; Costs; Distillation; Economic analysis; Energy utilization; Ethanol; Fuels; Gasoline; Greenhouse gases; Internal combustion engines; Life cycle; Motor transportation; Plants (botany); Roads and streets; Taxation; Bio-ethanol production; Environmental assessment; Limitation factors; Performance and emissions; Sri Kanji 1 cassava; Sustainable improvement; Techno-Economic analysis; Transportation sector; Bioethanol